PERKEMBANGAN MAZHAB SHOHABI DALAM ISLAM - Encum Sumirah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to explain the development of the shohabi school in the Islamic world, as it is known that the Sahabai school is still a debate among scholars about its legality as a syar'i proposition, but until now there are still many cases whose sources refer to the shahabi school. This study uses a literature review, namely a study that focuses on literature review that is closely related to the development of the shohabi school in the Islamic world. The results of the study showed that the shohabi school was the opinion of friends about the law of a case after the death of the Prophet. The emergence of this school was due to the emergence of new cases after the death of the apostle which had never happened at the time of the Prophet Muhammad. The Shohabi school has developed along with the changing times. However, the shahabi school as a school that was born from friends who were not free from sin, so many people doubted it, but the virtue of this shahabi school is that it comes from friends who lived during the apostle's time and took part in resolving the case of the apostle's time by adhering to stick to the Qur'an and Sunnah. The recommendation from the results of this study is that the development of the dynamics of people's lives is in line with efforts to fulfill legal legality which can truly guarantee the survival of the community in the corridor of Islamic religious values, thus sources of law are absolutely necessary in people's lives as an effort to maintain harmonious life.